Motivational Illocutions of "Laskar Pelangi" Novel by Andrea Hirata for Teachers and Students - Patur Rahman; Nurfajri Ningsih (International Journal in Applied Linguistics of Parahikma, 2023)
It is crucial for the teacher to motivate the pupils in the classroom because doing so could set the stage for their further learning. Generally, teachers often run out of ideas to motivate students and distress them to find authentic material to make the teaching process more interesting. This research centralized the explanation on literature, specifically the Laskar Pelangi Novel. The data were collected qualitatively using the discourse analysis approach by read and considering the illocution aspects of Searle in the novel. The data analysis passed through 12 extracts and had been elaborated by related theories. The result of this research found many kinds of motivational illocution in the novel, consisting of assertions formed in motivational boast, directives in advice, command, threat, and recommend form, expressives such as worrying, praising, confirming, and welcoming sentence sequences, and declaration form, which is composed of resigning and naming. Further results intended to convey motivational illocution by Bu Muslimah's character in the novel showed discourse analysis results in order to influence teachers in the general classroom according to the character. The advantage of this research is that it teaches speech act in a motivational way by using a novel storyline to create an uncommon atmosphere in the classroom. Furthermore, this is an important contribution for the teacher as authentic material from literature source which is not only useful in entertainment but also in general classroom learning. Therefore, teachers can teach speech act or sentence analysis by Laskar Pelangi and also take some storylines as examples to prove that teachers are not only to teach but also to motivate. Keywords: Motivational Illocution; authentic material; speech act; assertive; expressive; directives; declaration; novel; education